Supporting youth 12–24 during the COVID-19 pandemic: how Foundry is mobilizing to provide information, resources and hope across the province of British Columbia. (March 2021) - Zenone, Marco Antonio; Cianfrone, Michelle; Sharma, Rebecca; Majid, Sanaa; Rakhra, Jasmine; Cruz, Kathryn; Costales, Stefanie; Sekhon, Monique; Mathias, Steve; Tugwell, Andrew; Barbic, Skye
Foundry is a province-wide network of integrated health and social service centres for young people aged 12–24 in British Columbia (BC), Canada. Online resources and virtual care broaden Foundry's reach. Its online platform – foundrybc.ca – offers information and resources on topics such as mental health, sexual wellness, life skills, and other content suggested by youth and young adults. The COVID-19 pandemic has presented significant and unique challenges to the youth and their families/caregivers served by Foundry. Disruptions to school, access to essential healthcare services such as counselling, familial financial security and related consequences has left young people with heightened anxiety. The Foundry team mobilized to respond to these extenuating circumstances and support BC youth and their families/caregivers during this hard time through three goals: (1) to amplify (and translate for young people and their families/caregivers) key messages released by government to support public health responses to the COVID-19 pandemic; (2) to develop content that supports the needs of young people and their families/caregivers that existed before COVID-19 and are likely to be exacerbated as a result of this pandemic; and (3) to develop and host opportunities through social media and website articles to engage young people and their families/caregivers by creating a sense of community and promoting togetherness and social connection during the COVID-19 pandemic. Each goal and plan integrated the leadership, feedback and needs of youth and their families through engagement with Foundry's provincial youth and family advisory committees. Our study evaluated Foundry's media response to the COVID-19 pandemic by recording/measuring (1) the website/social content created, including emerged thematic topic areas; (2) the process of topic identification through engagement with youth and young adults; (3) the social and website analytics of the created content; and (4) the constant, critical team-reflection of our response to the pandemic. Following measurement and reflection, our team offers recommendations to health promotion organizations for future preparedness.